INCLUSIVE SOCIETY AS A NORMATIVE IDEAL: FROM THE THEORY OF JUSTICE TO THE PRACTICE OF EQUALITY - Choriyeva Madina Aliyevna (Web of Journals Publishing, 2026)
In the article "Inclusive Society as a Normative Ideal: From the Theory of Justice to the Practice of Equality," inclusion is considered not only as a social policy, but primarily as a philosophical and normative project of modernity. The theoretical basis of the research is the concepts of justice by John Rawls, discursive ethics by Jürgen Habermas, and the approach to the possibilities of Amartya Sen. It is shown that an inclusive society is formed at the intersection of the principles of equal freedoms, institutional compensation for social inequality, and recognition of human dignity as an unconditional value.
Keywords: Healthy lifestyle, philosophical anthropology, New Uzbekistan, health consciousness, human development, value systems, social well-being, modernization, public health culture, ethical norms, socio-cultural transformation.